Refining and psychometric evaluation of the falling risk assessment tool in ophthalmology inpatients - Muling Li; Chunmei Li; Qinghui Huang; Hongzhen Zhou; Ling Xie; Fangni Chen; Shaoqin Lin; Juan Yang (Wiley, 2023)
Abstract Aims The aim of this study was to refine the Falling Risk Assessment Tool in Ophthalmology Inpatients (FRAT) and assess its psychometric properties. Design A cross‐sectional design was used. Methods A convenience sample of 730 patients in the ophthalmology department was recruited in a level A tertiary hospital in Guangdong Province from July 2021 to January 2022. Data were analysed using item analysis, interrater reliability, content validation, internal consistency reliability and exploratory factor analysis. Results Five factors were extracted, accounting for 63.039% of the variance. The interrater reliability of the tool was 0.97. Cronbach's α was 0.658. The I‐CVI was 0.75-1.00, the S‐CVI/UA was 0.95 and the adjusted mean values of Kappa for indicators ranged from 0.72 to 1.00, as evaluated by the expert group. The FRAT showed satisfactory reliability and validity, and can be used to measure the fall risk assessment in ophthalmology inpatients. Patient or Public Contribution After explaining the purpose, the patients received our fall risk assessment and answered the corresponding questionnaire questions.